TA-Ag / Pd nano material as well as preparation method and application thereof

By preparing TA-Ag/Pd nanomaterials, the problems of poor stability and limited antibacterial effects of nano-anti-anti-bacterial materials are solved, and effective inhibition of E. coli and S. aureus is achieved, with significant antibacterial properties and wide application prospects.

CN120286721APending Publication Date: 2025-07-11NANCHANG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510408025.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-02
Publication Date
2025-07-11

AI Technical Summary

Technical Problem

The existing nano-anti-bacterial materials have poor stability and limited antibacterial effects, which limit their further application and development.

Method used

TA-Ag/Pd nanomaterials were prepared by Na2PdCl4, HCl and tanninic acid solutions. By vortex mixing, constant temperature treatment and centrifugal drying, stable TA-Ag/Pd complex was formed to avoid agglomeration and enhance antibacterial properties.

Benefits of technology

The prepared TA-Ag/Pd nanomaterials have significant effects in antibacterial aspects, can effectively inhibit the growth of E. coli and S. aureus, have good stability and wide application potential, and are suitable for antibacterial, environmental protection, medical and food packaging fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120286721A_ABST
    Figure CN120286721A_ABST
Patent Text Reader

Abstract

The invention discloses a tannic acid-silver palladium (TA-Ag / Pd) nano material and a preparation method and application thereof, and belongs to the technical field of biological materials.The method comprises the steps that Na2PdCl4 is added into water containing HCl, and a palladium solution is obtained; the palladium solution and the silver nitrate solution are added into the tannic acid solution for vortex mixing, and a mixed solution is obtained; and carrying out constant-temperature treatment on the mixed solution, washing, centrifuging and drying to obtain the TA-Ag / Pd nano material. The preparation method provided by the invention is mild in reaction condition, simple and convenient in preparation process, short in time and high in efficiency, and the prepared TA-Ag / Pd nano-material shows a remarkable antibacterial effect, can effectively inhibit growth of bacteria such as escherichia coli and staphylococcus aureus, is suitable for the fields of medical instruments, food packaging, environmental protection and the like, and has wide application prospects. The method has remarkable application advantages and wide market potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the technical field of biomaterials, and particularly relates to a TA-Ag / Pd nanomaterial, its preparation method and application. Background Art

[0002] Globally, bacterial infections continue to pose a severe health threat, making the research and innovation of treatment strategies particularly important. As a traditional treatment method, antibiotics have played an irreplaceable role in combating bacterial infections. However, the abuse and overuse of antibiotics have led to the rapid emergence of drug-resistant bacteria. This trend not only weakens the clinical efficacy of antibiotics but also greatly increases the complexity and challenge of treating bacterial infections. Therefore, exploring and developing new antibacterial materials to replace or assist traditional antibiotics has become an urgent need in current medical research.

[0003] Due to their unique physical and chemical properties, nanomaterials have shown great application potential in multiple fields. Especially in the antibacterial field, metal nanomaterials have received extensive attention due to their significant antibacterial effects. However, these materials have some challenges in practical applications, such as easy aggregation, poor stability, and limited antibacterial effects, which limit their further application and development. Summary of the Invention

[0004] The purpose of this application is to provide a TA-Ag / Pd nanomaterial, its preparation method and application, which can solve the problems of poor stability and limited antibacterial effect of existing nano antibacterial materials.

[0005] To solve the above technical problems, this application is implemented as follows: In the first aspect, an embodiment of this application provides a preparation method of a TA-Ag / Pd nanomaterial, and the method includes: Adding Na2PdCl4 into water containing HCl to obtain a palladium solution; Adding the palladium solution and silver nitrate solution into tannic acid solution and mixing them by vortex to obtain a mixed solution; Performing constant temperature treatment, washing, centrifuging and drying on the mixed solution to obtain the TA-Ag / Pd nanomaterial.

[0006] Further, the volume ratio of Na2PdCl4, HCl and water in the palladium solution is 450-550:15-20:450-500; the concentration of Na2PdCl4 in the palladium solution is 0.08 M-0.12 M, and the concentration of HCl in the palladium solution is 0.8 M-1.2 M.

[0007] Even further, the volume ratio of Na2PdCl4, HCl and water in the palladium solution is 500:16:484.

[0008] The concentration of Na2PdCl4 in the palladium solution is 0.1 M, and the concentration of HCl in the palladium solution is 1 M.

[0009] Furthermore, the ratio of silver nitrate to water in the silver nitrate solution is 7 - 9 mg: 0.5 - 1.5 mL.

[0010] Even further, the ratio of silver nitrate to water in the silver nitrate solution is 8.5 mg: 1 mL.

[0011] Furthermore, the ratio of tannic acid to water in the tannic acid solution is 90 - 110 mg: 5 - 10 mL.

[0012] Even further, the ratio of tannic acid to water in the tannic acid solution is 100 mg: 8 mL.

[0013] Furthermore, the vortex rotation speed is 550 rpm - 650 rpm, and the vortex time is 18 - 22 min.

[0014] The centrifugation speed is 7000 r / min - 9000 r / min, the centrifugation time is 4 min - 6 min, and the number of centrifugation times is 2 - 4 times.

[0015] Even further, the vortex rotation speed is 600 rpm, and the vortex time is 20 min.

[0016] Even further, the centrifugation speed is 8000 r / min, the centrifugation time is 5 min, and the number of centrifugation times is 3 times.

[0017] Furthermore, the steps of performing constant temperature treatment on the mixed solution specifically include: Placing the mixed solution in a constant temperature bath at 35°C - 40°C and reacting for 7 - 9 h to obtain the mixed solution after constant temperature treatment.

[0018] Furthermore, the centrifugation speed is 7000 r / min - 9000 r / min, the centrifugation time is 4 min - 6 min, and the number of centrifugation times is 2 - 4 times.

[0019] Even further, placing the mixed solution in a constant temperature bath at 37°C and reacting for 8 h to obtain the mixed solution after constant temperature treatment.

[0020] In the second aspect, the present application provides a TA - Ag / Pd nanomaterial, which is prepared by the above - mentioned preparation method of the TA - Ag / Pd nanomaterial.

[0021] In the third aspect, the present application provides an application of the above - mentioned TA - Ag / Pd nanomaterial in the preparation of antibacterial products.

[0022] Furthermore, the antibacterial product includes a composition of TA-Ag / Pd nanomaterials and peroxide.

[0023] Furthermore, the antibacterial product can effectively inhibit E. coli and S. aureus from growing.

[0024] This application has at least one of the following beneficial effects: (1) The TA-Ag / Pd nanomaterials prepared in this application show significant antibacterial effects and can effectively inhibit the growth of bacteria such as E. coli , S. aureus .

[0025] (2) The TA-Ag / Pd nanomaterials prepared in this application use natural tannic acid as a ligand, avoiding the use of harmful substances in chemical synthesis, meeting the requirements of green chemistry and environmental protection.

[0026] (3) The TA-Ag / Pd composite materials prepared in this application have good stability and can still maintain strong antibacterial activity after multiple uses, being suitable for long-term applications.

[0027] (4) The TA-Ag / Pd nanomaterials prepared in this application are not only applicable to the antibacterial field but can also be widely used in multiple industries such as environmental protection, medical treatment, and food packaging, having great market application potential. Description of the Drawings

[0028] Figure 1 is the preparation schematic diagram of the TA-Ag / Pd nanomaterials provided in Example 1 of this application.

[0029] Figure 2 is the scanning electron microscope (SEM) image of the TA-Ag / Pd nanomaterials provided in Example 1 of this application.

[0030] Figure 3 is the antibacterial effect (bactericidal rate) graph of the test solutions with different concentrations provided in Example 2 of this application against E. coli .

[0031] Figure 4 is the antibacterial effect (bactericidal rate) graph of the test solutions with different concentrations provided in Example 2 of this application against S. aureus .

[0032] Figure 5 is the verification of the antibacterial effect (bactericidal rate) of the enhanced peroxidase activity of TA-Ag / Pd provided in Example 2 of this application against E. coli .

[0033] Figure 6 is the verification of the antibacterial effect of the enhanced peroxidase activity of TA-Ag / Pd provided in Example 2 of this application againstS. aureus Verification of antibacterial effect (bactericidal rate).

[0034] Figure 7 This is for verifying the enhancement of TA-Ag / Pd peroxidase activity provided in Example 2 of the present application for E. coli and S. aureus Antibacterial effect diagram. Specific implementation mode

[0035] Next, the technical solutions in the embodiments of the present application will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present application without creative efforts shall fall within the protection scope of the present application.

[0036] Example 1 Prepare TA-Ag / Pd nanomaterials, including the following steps: (1) Add 500 μL of Na2PdCl4 to deionized water containing 16 μL of HCl to obtain a palladium solution. The volume of Na2PdCl4 is 500 μL, the volume of HCl is 16 μL, and the volume of deionized water is 484 μL. The concentrations of Na2PdCl4 and HCl in the palladium solution are 0.1 M and 1 M respectively.

[0037] (2) Weigh 8.5 mg of silver nitrate and dissolve it in 1 ml of deionized water to make it completely dissolved and evenly dispersed to obtain a silver nitrate solution.

[0038] (3) Measure 8 mL of deionized water with a measuring cylinder and add it to a 50 mL conical flask placed on a magnetic stirrer.

[0039] (4) Weigh 100 mg of tannic acid and pour it into the deionized water under magnetic stirring to make it completely dissolved and evenly dispersed to obtain a tannic acid solution.

[0040] (5) Pour the palladium solution and the silver nitrate solution into the tannic acid solution under magnetic stirring, and immediately mix them by vortex. The mixed solution is obtained, where the vortex rotation speed is 600 rpm and the vortex time is 20 min.

[0041] (6) Subsequently, place the mixed solution in a 37°C constant temperature bath and react for 8 h to obtain the mixed solution after constant temperature treatment.

[0042] (7) Wash the mixed solution after constant temperature treatment with ultrapure water, and centrifuge it at 8000 rpm / min for 5 min, repeating 3 times. Finally, freeze-dry it at -55°C for 24 h to obtain TA-Ag / Pd nanomaterials.

[0043] Explore the preparation principle of TA-Ag / Pd nanomaterials and scan TA-Ag / Pd nanomaterials with an electron microscope.

[0044] Experimental results: Figure 1 Figure is the preparation principle diagram of TA-Ag / Pd nanomaterials. Under acidic conditions (pH adjusted by HCl), TA reduces Ag + and Pd 2+ in-situ to Ag / Pd nanoparticles through polyphenol groups, and at the same time, the metal particles are wrapped through coordination bonds and cation-π interactions to form a stable TA-Ag / Pd composite.

[0045] As Figure 2 shown, the scanning electron microscope results show that the nanomaterial particles are irregular in shape and evenly distributed, indicating that good dispersion is achieved during the preparation process, avoiding significant aggregation. In addition, the particle surface has rough textures, which may be due to the interaction between polyphenol molecules and metal nanoparticles. This surface structure can enhance the antibacterial performance of the material by increasing the contact area with microorganisms.

[0046] Example 2 Antibacterial performance test: 1. Determination of bactericidal rate (1) Perform subculture on E. coli and S. aureus the night before. After inoculation, place the bacterial liquid in a constant temperature shaker at 37 °C and 180 rpm and culture overnight. Prepare LB solid medium and pour plates.

[0047] (2) Take out the bacterial liquid cultured overnight from the 37 °C incubator, dilute the bacterial liquid cultured overnight to 10 7 CFU / mL with PBS and set aside. Add 100 μL of E. coli or S. aureus bacterial liquid, the corresponding volume of the test solution and PBS buffer in a sterile centrifuge tube and incubate for 4 h. Among them, the concentration gradients of the test solutions for E. coli inhibition are: 0, 0.2, 0.4, 0.8, 1.6, 3.2 μg / mL. The concentration gradients of the test solutions for S. aureus inhibition are 0, 4, 8, 16, 32, 64 μg / mL. The detailed grouping is shown in the following table: Table 1 Experimental grouping for the determination of bactericidal rate ① Control group: Add 100 μL of bacterial liquid and 900 μL of PBS buffer as the control group.

[0048] ②TA-Ag group: Add 100 μL of bacterial solution, 100 μL of TA-Ag nano antibacterial material solution with different concentration gradients, and 900 μL of PBS buffer solution.

[0049] ③TA-Pd group: Add 100 μL of bacterial solution, 100 μL of TA-Pd nano antibacterial material solution with corresponding concentration gradients, and 800 μL of PBS buffer solution.

[0050] ④TA-Ag / Pd group: Add 100 μL of bacterial solution, 100 μL of TA-Ag / Pd nano antibacterial material solution with corresponding concentration gradients, and 800 μL of PBS buffer solution.

[0051] (3) After incubation, take samples and dilute them for spot plate counting and plate spreading.

[0052] (4) Calculate the bactericidal rate according to the results of spot plate counting.

[0053] Bactericidal rate = (number of colonies in the control group - number of colonies in the experimental group or control group) / number of colonies in the control group × 100%.

[0054] 2. Peroxidase activity enhancement experiment (1) The E. coli and S. aureus strains were subcultured the night before. After inoculation, the bacterial solution was placed in a constant temperature shaker at 37 °C and 180 rpm and cultured overnight. Prepare LB solid medium and pour plates.

[0055] (2) Take out the E. coli and S. aureus bacterial solutions cultured overnight from the 37 °C incubator. Dilute the E. coli and S. aureus bacterial solutions cultured overnight with PBS to 10 7 CFU / mL for standby. Add 100 μL of E. Coli bacterial solution or S. aureus bacterial solution and the corresponding volume of the test solution and PBS buffer solution and incubate for 4 h. Among them, the concentration of H2O2 used is 250 μM; the concentration of the test solution for E. coli inhibition is 1.6 μg / mL; the concentration gradient of the test solution for S. aureus inhibition is 32 μg / mL. The detailed grouping is shown in the following table: Table 2 Grouping of peroxidase activity enhancement experiment ① Control group: Add 100 μL of bacterial solution and 900 μL of PBS buffer solution as the control group.

[0056] ②H2O2 group: add 100 μL bacterial solution, 100 μL 250 μM H2O2 solution and 800 μL PBS buffer.

[0057] ③TA-Ag / Pd group: 100 μL bacterial solution and 100 μL Pd solution with a concentration of 1.6 μg / mL ( E. coli ) or 32 μg / mL ( S. aureus ) of TA-Ag / Pd nano antibacterial material solution and 800 μL PBS buffer.

[0058] ④H2O2+TA-Ag / Pd group: 100 μL bacterial solution, 100 μL 250 μM H2O2 solution, and 100 μL 1.6 μg / mL ( E. coli ) or 32 μg / mL ( S. aureus ) of TA-Ag / Pd nano antibacterial material solution and 700 μL PBS buffer.

[0059] (3) After incubation, take a sample and dilute it for spot counting and plate spreading.

[0060] (4) Calculate the sterilization rate based on the spot plate counting results.

[0061] Sterilization rate = (number of colonies in the control group - number of colonies in the experimental group or control group) / number of colonies in the control group × 100%.

[0062] Experimental results: Figure 3 and Figure 4 The test solutions with different concentrations are E. coli and S. aureus The results show that compared with the control group, TA-Ag / Pd nanomaterials have a E. coli and S. aureus Both showed good antibacterial effects, and the bactericidal effect of the TA-Ag / Pd group was significantly better than that of the TA-Ag group and TA-Pd group.

[0063] Figure 5 , Figure 6 , Figure 7 The experimental results of verifying the enhanced antibacterial effect of TA-Ag / Pd peroxidase activity are shown in the figure. It can be seen from the figure that compared with the control group, the use of H2O2 alone and the use of TA-Ag / Pd nanomaterials alone have certain antibacterial effects, among which the antibacterial effect of TA-Ag / Pd nanomaterials alone is significantly better than that of H2O2 alone. After using H2O2 and TA-Ag / Pd nanomaterials at the same time, the antibacterial effect is significantly enhanced, which can effectively inhibit E. coli andS. aureus Growth

[0064] It can be inferred that the TA-Ag / Pd nanomaterial can mimic the activity of natural peroxidase. After combined action with H2O2, its peroxidase activity is enhanced, further catalyzing the decomposition of H2O2 into water and oxygen (H2O2 → H2O + O2), and highly reactive hydroxyl radicals (·OH) will be generated during the reaction process. This is a strong oxidant that can destroy the cell wall and cell membrane of bacteria, leading to bacterial death. This synergistic effect indicates that the combined use of TA-Ag / Pd nanomaterials and H2O2 has significant application potential in the preparation of antibacterial products.

[0065] The embodiments of the present application have been described above in conjunction with the accompanying drawings. However, the present application is not limited to the above specific embodiments. The above specific embodiments are merely illustrative rather than restrictive. Under the inspiration of the present application, those of ordinary skill in the art can also make many forms without departing from the purpose of the present application and the scope protected by the claims, and all of them belong to the protection scope of the present application.

Claims

1. A preparation method of TA-Ag / Pd nanomaterials, characterized in that, It includes the following steps: Add Na2PdCl4 into water containing HCl to obtain a palladium solution; Add the palladium solution and silver nitrate solution into tannic acid solution and mix them by vortex to obtain a mixed solution; Subject the mixed solution to constant temperature treatment, washing, centrifugation and drying to obtain TA-Ag / Pd nanomaterials.

2. The method according to claim 1, wherein The volume ratio of Na2PdCl4, HCl and water in the palladium solution is 450-550:15-20:450-500; The concentration of Na2PdCl4 in the palladium solution is 0.08 M-0.12 M, and the concentration of HCl in the palladium solution is 0.8 M-1.2 M.

3. The method according to claim 1, characterized in that, The ratio of silver nitrate to water in the silver nitrate solution is 7-9 mg:0.5-1.5 mL.

4. The method according to claim 1, wherein The ratio of tannic acid to water in the tannic acid solution is 90-110 mg:5-10 mL.

5. The method according to claim 1, characterized in that the vortex rotation speed is 550 rpm-650 rpm, and the vortex time is 20 min; the centrifugation rotation speed is 7000 r / min-9000 r / min, the centrifugation time is 4 min-6 min, and the number of centrifugation times is 2-4 times.

6. The method according to claim 1, characterized in that The step of subjecting the mixed solution to constant temperature treatment specifically includes: Place the mixed solution in a constant temperature bath at 35°C-40°C and react for 7-9 h to obtain the mixed solution after constant temperature treatment.

7. A TA-Ag / Pd nanomaterial, characterized in that, Prepared by the preparation method of TA-Ag / Pd nanomaterials according to any one of claims 1-6.

8. An application of the TA-Ag / Pd nanomaterials according to claim 7 in the preparation of antibacterial products.

9. The application according to claim 8, wherein The antibacterial product includes a composition of TA-Ag / Pd nanomaterials and peroxide.

10. The application according to claim 8 or 9, characterized in that, The antibacterial product can effectively inhibit E. coli and S. aureus from growing.

Citation Information

Cited By

  • Antibacterial nano-particles based on tannic acid and sophocarpidine as well as preparation method and application of antibacterial nano-particles

    CN121891382A